OP83 Value Assessment Framework: Evidence-Informed Deliberative Processes. (2017) - Tummers, Marcia; Baltussen, Rob; Jansen, Maarten; Bijlmakers, Leon; Grutters, Janneke; Kluytmans, Anouck; Reuzel, Rob; van der Wilt, Gert Jan
Abstract : INTRODUCTION: Priority setting in health care has been long recognized as an intrinsically complex and value-laden process. Yet, Health Technology Assessment (HTA) agencies presently employ value assessment frameworks that are ill-fitted to capture the range and diversity of stakeholder values, and thereby risk to compromise the legitimacy of their recommendations. We propose 'evidence-informed deliberative processes' as an alternative framework with the aim to enhance this legitimacy. METHODS: The framework is based on an integration of two increasingly popular and complementary frameworks for priority setting: multi-criteria decision analysis (MCDA) and accountability for reasonableness (A4R), Evidence-informed deliberative processes are, on the one hand, based on early, continued stakeholder deliberation to learn about the importance of relevant social values. On the other hand, they are based on rational decision-making – through evidence-informed evaluation of the identified values. RESULTS: The framework has important implications for how HTA agencies should ideally organize their processes. Firstly, HTA agencies should take the responsibility to organize stakeholder involvement. Second, agencies are advised to integrate their assessment and appraisal phase, allowing for the timely collection of evidence on values that are considered relevant. Third, HTA agencies should subject their specification of decision-making criteria to public scrutiny. Fourth, agencies are advised to use a checklist of potentially relevant criteria, and to provide argumentation how each criterion affected the recommendation. Fifth, HTA agencies must publish their argumentation and install options for appeal. CONCLUSIONS: Adopting 'evidence-informed deliberative processes' as a value assessment framework could be an important step forward for HTA agencies to optimize the legitimacy of their priority setting decisions. Agencies can incorporate elements according to their needs and affordances.